2021
DOI: 10.3390/w13152135
|View full text |Cite
|
Sign up to set email alerts
|

Mapping of Coastline Changes in Athens Riviera over the Past 76 Year’s Measurements

Abstract: Mapping of coastline changes assists in coastal development and monitoring. Athens Riviera, located in the southwestern coastal zone in Attica in central Greece, has undergone major and radical changes generated by human interference during the last decades. The aim of this paper is to map record and measure the coastline changes in Athens Riviera over the past 76 years. Aerial photographs and satellite images from 1945 to 2021 as well as geographic information system (GIS) techniques were used to depict the s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 40 publications
0
5
0
Order By: Relevance
“…Figure 2 shows the approach used in our study. First, GPS data and satellite images (Sentinel-2 and Google Earth) were collected and used as an integral means [31] for observing the evolution of the sand spit. Wave data were also collected in the first step of the research.…”
Section: Methodsmentioning
confidence: 99%
“…Figure 2 shows the approach used in our study. First, GPS data and satellite images (Sentinel-2 and Google Earth) were collected and used as an integral means [31] for observing the evolution of the sand spit. Wave data were also collected in the first step of the research.…”
Section: Methodsmentioning
confidence: 99%
“…In the Athens Riviera, the coastline was enhanced by 40% from 1945 to 2021, while land reclaimed to the sea area now approached 2.7 km 2 because of human interventions. The growth of urban fronts in the coastal area resulted in this artificial increase of coastline length [73].…”
Section: Major Reasons For Coastline Changes In the Ghmgbamentioning
confidence: 99%
“…Research conducted on the East Coast of South Korea found that the artificial structures constructed along the coast have not completely solved or stopped erosion but shifted it from one location to another [14]. On the contrary, work by Skilodimou et al [15] shows how coastlines have been enhanced by 40% over the last 76 years due to human interventions, in this case, earth filling.…”
Section: Introductionmentioning
confidence: 99%